EXPLORING THE OFFICIAL WEBSITE: HOW INDONESIA MINING INDUSTRY COMMUNICATE THEIR CORPORATE SOCIAL RESPONSIBILITY ACTION - Ati Harmoni (Jurnal Ilmiah Ekonomi Bisnis, 2012)
In this paper, CSR communication are investigated through the analysis of websites, by exploring companies which are operating in Indonesia in mining industry. These companies are categorized in Business Index-27. Based on the analysis, it is found that a number of features discovered.Keywords: CSR communication, mining industry, website.